The Mathnawi of Jalaluddin Rumi - The_Mathnawi... (S. Sajid ali For Adam Publishers & Distributors, 1996)
ir, Jilid [1-2]=c.1-2; Jilid [3-4]=c1.2; Jilid [3-6]=c1; Jilid 4=c1; Jilid [5-6]=c.1-2; jilid 6=c.1/why, jil [1-2]=c.3